Die Studentverpieegster As Adolessent - S.P. Human (AOSIS, 1978)
The student nurse is no exception to the rule that for an adolescent this stage is a time of uncertainty and is full of problems. Her status in the social hierarchy is an uncertain one: She is neither a child nor an adult and yet her patients are mainly adult. She lives through a stage of change, experiences frustration in the face of demands for conformity. She encounters the problem of self-identification. What is this " self" that she must learn to recognise and accept? It is important that tutors, ward sisters and matrons should be aware of all this and be competent to help the student nurse through adolescence. She must be able to develop into a mature, responsible,professional member of the community.